PERAN SUPPLY CHAIN MANAGEMENT DALAM SISTEM PRODUKSI DAN OPERASI PERUSAHAAN - Agus Widyarto (Benefit: Jurnal Manajemen dan Bisnis, 2012)
Supply Chain Management is a set of approaches for the efficient integration of suppliers,manufacturing, warehouse and storage, so that goods are produced and distributed in the rightamount, the right location, the right time, to minimize costs and provide service to the customersatisfaction. At this time many companies are implementing Supply Chain Management to improvethe competitiveness of the company to another. Supply Chain Management is a strategic competitivetool for companies that make bersainganya logistical problems as a strategy to win the competition.The purpose of making this paper is to investigate the role of Supplay Chain Management inproduction systems and operations within the company that allows you to provide value to consumers in terms of availability and speed of service. So that consumers will feel the advantages of theproduct, although physically relatively similar to other products.